Plant growth promoting and antimicrobial functionalities of rhizosphere Pseudomonas species in flooded rice soils of coastal Odisha. Issue 2 (5th November 2022) - Das, Jyotirmayee; Dangar, Tushar Kanti; Adhya, Tapan Kumar; Panigrahy, Madhusmita
Abstract: Microbiome‐plant interactions have been carried out all over the world in the hunt for growth‐promoting bacteria to augment agriculture. Therefore, diversity and plant growth promotion (PGP) functions of the predominant Gram‐negative bacteria, Pseudomonas spp., of the flooded rice rhizosphere were analyzed. Out of three most potent plant growth promoting rhizobacteria (PGPR), phenotypic identity of two isolates (TB324, 325) was P. putida but another one (TB326) was P. chorii . Nevertheless, 16S rRNA phylogram claded all 3 (TB324, 325, and 326) potent isolates with P. putida . The isolates solubilized tricalcium phosphate (132.42–162.23 µg/ml), fixed nitrogen (75.46–325.41 nM ethylene/g bact./h), produced IAA (12.06–68.49 µg/ml), salicylic acid (6.54–6.75 µg/ml), hydrogen cyanide (0.03–0.05 ΔA625 ), siderophore (3.75–7.55 µM/ml), protease, cellulase and ammonia (TB326). Furthermore, the organisms differentially antagonized the phytopathogenic fungi viz. Xanthomonas oryzae, Magnoportha grisea, Aspergillus niger, Fusarium oxysporum, Helminthosporium sp., Curvularia sp. and Rhizoctonia solani, as well as, entomopathogens like Fusarium, Nomurae, Verticillium, and Paecilomyces spp., and Beauveria bassiana . TB324, 325, and 326 tolerated abiotic stresses like pH 3–12, NaCl 9%–12%, sea salt 14% and sodium acetate 0.9–1.0 M. Besides, the organisms possessed different phenazine genes and their cellular protein constituents were comparable. All Pseudomonas isolates enhanced growth of potted rice plants over control. TB 326 enhanced maximum root (18.9 ± 0.25 cm) and shoot (73.4 ± 0.81 cm) growth.